2019
DOI: 10.1111/infa.12293
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Patterns of Regulatory Behavior in the Still‐Face Paradigm at 3 Months

Abstract: The current study addressed two aims: (1) to describe different patterns of infant regulatory behavior during the Face‐to‐Face Still‐Face (FFSF) paradigm at 3 months of age and (2) to identify specific, independent predictors of these patterns from an a priori set of demographic, infant (e.g., temperament), and maternal (e.g., sensitivity) variables. Analyses were based on data collected for 121 mother–infant dyads assessed longitudinally in the newborn period and again at 3 months. In the newborn period, infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 43 publications
5
18
0
Order By: Relevance
“…Moreover, in this study maternal sensitivity observed during free play was highly associated with a Social-Positive Oriented pattern and predicted infant regulatory patterns in the FFSF. These findings are consistent with those reported in prior work with infants born full-term [4,17,24,27]. In line with international research, our results suggest that mothers who were more sensitive in the free play (e.g., responsive behavior and positive engagement) exhibited greater ability to comfort their infant in the FFSF, while the infant responds with cooperative behavior.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, in this study maternal sensitivity observed during free play was highly associated with a Social-Positive Oriented pattern and predicted infant regulatory patterns in the FFSF. These findings are consistent with those reported in prior work with infants born full-term [4,17,24,27]. In line with international research, our results suggest that mothers who were more sensitive in the free play (e.g., responsive behavior and positive engagement) exhibited greater ability to comfort their infant in the FFSF, while the infant responds with cooperative behavior.…”
Section: Discussionsupporting
confidence: 92%
“…Parents-infant exchange is based on co-regulation, where both partners need to express their intentions, to acknowledge the intentions of the partner, and to scaffold the partner's actions so that each partner can achieve their goals. Supporting these hypotheses, several studies found a link between the quality of mother-infant interactions and infant strategies for emotional regulation (e.g., [4,[17][18][19]).…”
Section: Introductionmentioning
confidence: 92%
“…Results from prior longitudinal studies show that the three infant regulatory patterns are stable from 3 to 9 months [ 7 ], affected by dyadic interactions [ 2 , 8 ], maternal representations of infant behavior [ 9 , 33 ], and infant birth status [ 2 ]. In the current cross-sectional study, findings regarding the associations of infant regulatory patterns with maternal interactive behavior, sociodemographics, and infant health were partially replicated in the Brazilian and Portuguese samples.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up studies suggest that these early-emerging regulatory behavior patterns are relatively stable from 3 to 9 months of age [ 7 ] and are associated with variations in maternal interactive behavior in other contexts [ 8 ], and infants’ attachment security at age one [ 10 , 11 ]. Despite the apparent relevance of these patterns for infants’ socioemotional development, very few studies have examined the distribution of these regulatory patterns outside US and European countries, or evaluated whether these patterns differ across countries or in different socio-demographic contexts.…”
Section: Introductionmentioning
confidence: 99%
“…No analyses were conducted to consider the impact of this variable. However, in studies such as Barbosa et al (2019) and Seixas et al (2017), maternal education did not present a significant association with maternal and infant interactive behaviors. Another limitation refers to the lack of analysis of maternal behaviors during the interaction with the infant in the context of FFSF, which could contribute to the discussion in a more comprehensive manner.…”
Section: Discussionmentioning
confidence: 75%